2021
DOI: 10.1007/978-3-030-90677-1_36
|View full text |Cite|
|
Sign up to set email alerts
|

CAERS: A Conversational Agent for Intervention in MOOCs’ Learning Processes

Abstract: Drets d'ús i reutilitzacióAquesta versió del manuscrit es fa disponible amb una llicència Creative Commons del tipus Atribució No Comercial No Derivades (CC BY-NC-ND) http://creativecommons.org/licenses/by-nc-nd/4.0, que permet baixar-la i compartir-la sempre que se'n citi l'autoria, però sense modificar-la ni utilitzar-la amb finalitats comercials. ConsultesSi creieu que aquest document infringeix els drets d'autor, contacteu amb l'equip de recerca:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For instance, both Kim et al [99] and Vytasek et al [105] presented an app to give feedback on the writing quality of students' essays before submission. Similarly, the conversational agent presented by Rossi et al [96] suggested learning materials to enhance students' comprehension, but if unsatisfactory, the student could ask for help from a tutor. The language tutor by Schlippe & Sawatzki [97] not only graded and gave feedback to students, but also utilised peer-review to support them, thus granting students some form of control over correct answers.…”
Section: ) Decision-makermentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, both Kim et al [99] and Vytasek et al [105] presented an app to give feedback on the writing quality of students' essays before submission. Similarly, the conversational agent presented by Rossi et al [96] suggested learning materials to enhance students' comprehension, but if unsatisfactory, the student could ask for help from a tutor. The language tutor by Schlippe & Sawatzki [97] not only graded and gave feedback to students, but also utilised peer-review to support them, thus granting students some form of control over correct answers.…”
Section: ) Decision-makermentioning
confidence: 99%
“…The language tutor by Schlippe & Sawatzki [97] not only graded and gave feedback to students, but also utilised peer-review to support them, thus granting students some form of control over correct answers. Still, in several articles, lecturers could also oversee the students' progress [44], [95], [96], [101].…”
Section: ) Decision-makermentioning
confidence: 99%
“…When a post in a discussion forum indicates that the student needs more than a message for pedagogical intervention, the agent may start and conduct an automatic interference (help) or ask the tutor for help. For automatic help, the subject in the message is recognized, and a pre-selected educational resource from the External Educational Resources repository is recommended to help the student with the content (ROSSI et al, 2021).…”
Section: Intervention Layermentioning
confidence: 99%
“…The educational domain is characterized by fragmented and specific solutions, where different organizations develop different services, tools, and plugins. Among the challenges of organizations that provide LMS are innovation, complexity, and security (Martin et al, 2018) (Rossi et al, 2021). The difficulty in maintaining LMSs with such a diversity of resources makes up an interesting scenario for Software Ecosystem (ECOS) perspective (Abdalla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rossi et al (83) designed a conversational agent that recommends resources to the learner according to his posts in the forum. Benjelloun Touimi et al…”
Section: Learning Elements Recommender Systemsmentioning
confidence: 99%